IMPLEMENTASI MEDIA COLOR BOX DALAM MATERI NILAI TEMPAT BILANGAN PADA PESERTA DIDIK KELAS I SEKOLAH DASAR - Rahmadini Arpen; Ira Wati Candra; Syamsidar Syamsidar; Puspita Sari Dewi; Vinessa Kanza; Jamal Okta Venri (CV. ADIBA ASIHA AMIRA, 2023)
This research aims to find out how Color Box media can be applied and increase students' enthusiasm for learning. So that learning is more interesting and students more easily understand learning. The method used is an experiment by giving pre-test and post-test to students. Make observations to see student activity. The research was carried out in two stages, namely action planning and action implementation. The results obtained are that students are enthusiastic about participating because all play an active role in the learning process and improve learning outcomes. The audio group had the most prominent activity compared to the other groups (visual and kinesthetic).